SEMINOMA ARISING FROM TESTICULAR AND OVARIAN REMNANTS HERALDS THE EMERGENCE OF A RARE MALE OVOTESTICULAR DISORDER OF SEXUAL DEVELOPMENT - Wei, Mak Woh; Yee, Teh When; Subramaniam, 1 Seetha Devi; Zain, Murizah Mohd; Zainal, Rohana; Ismail, Shartiyah; Merican, Nor Shaffinaz Yusoff Azmi; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Ovotesticular Disorder of Sex Development (OT DSD) or true hermaphroditism is a very rare subset of DSD and accounts for only 5% of cases. It has great phenotypic variability and poses diagnostic challenge to clinicians. It usually presents in childhood with ambiguous genitalia, characterized by histologic demonstration of ovarian and testicular tissues within the same individual. RESULTS We describe a 22-year-old man with OT DSD complicated by seminoma. He was delivered preterm with ambiguous genitalia and was lost to follow-up. He was raised as a female, at 14 years old, his teachers referred him due to concerns of male phenotype while participating in competitive sports. Phenotypically, he was a developed male with a micropenis, hypospadia, left scrotal cystic structure and empty right scrotum. Chromosomal analysis revealed 46XY and presence of SRY gene. Radiological imaging at age 16 showed fully developed Mullerian structures, with a single cervix and incomplete septate uterus, and an oval structure suggestive of testes at the left hemipelvis. Cysto-genitoscopy demonstrated normal urethra without prostatic urethra, opening at posterodistal bladder neck with blood clots likely representing the vagina. Laparoscopy identified tubulo-nodular structure inside the pelvis suggestive of vas deferens with suspicious early malignant changes. Wolffian remnant and bicornuate uterus were present with a right Fallopian tube with suspicious hydro-corpus. He was advised surgery, however, he defaulted again. He consulted again at age 22 due to pyuria, suprapubic pain and painless cyclical haematuria. Imaging studies demonstrated pyometra, bulky left ovary and bilateral undescended testes suspicious of malignant transformation. Exploratory laparotomy, gonadectomy, subtotal hysterectomy and left orchidectomy were performed. Histopathological examination revealed seminomas arising from testicular and ovarian remnants with suppurative inflammation in the uterus. He was provided testosterone replacement post operatively, and received chemotherapy (etoposide, bleomycin and platinum). CONCLUSION The complexity of the case exemplified the pivotal role of multidisciplinary input from various specialties.